2006
DOI: 10.1159/000095415
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Growth Rate of Lung Metastatic Lesions after Splenectomy in Mice

Abstract: Background: The effect of splenectomy on hematogenous metastases of malignant tumors remains controversial. The aim of this study was to clarify the effect of splenectomy on hematogenous metastases in an animal model. Methods: Colon 26 cancer cells were inoculated into the lateral tail vein of 90 mice. The mice were then assigned to a splenectomy group or a control group. Lung weight, number of lung metastases, size of metastatic nodules, and serum vascular endothelial growth factor (VEGF) and basic fibroblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 53 publications
2
5
1
Order By: Relevance
“…However, it causes smaller and fewer hematogenous breast cancer lung metastases. In line, in a subcutaneously inoculated lung cancer and in a colorectal CT26 tail vein injection model, splenectomy also reduced the number of lung metastases. In contrast, splenectomy in a portal vein injection model using the same CT26 tumor cell line caused a higher number of liver metastases, instead of its inhibition.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, it causes smaller and fewer hematogenous breast cancer lung metastases. In line, in a subcutaneously inoculated lung cancer and in a colorectal CT26 tail vein injection model, splenectomy also reduced the number of lung metastases. In contrast, splenectomy in a portal vein injection model using the same CT26 tumor cell line caused a higher number of liver metastases, instead of its inhibition.…”
Section: Discussionsupporting
confidence: 91%
“…The literature on the role of splenectomy in tumor progression and metastasis remains inconclusive. There are studies showing that splenectomy plays a role in (i) promoting [16][17][18][19] or (ii) inhibiting tumor growth and metastasis 10,11,[20][21][22][23][24][25] or (iii) not influencing tumor progression at all 26 ; highlighting its multifaceted role during malignant development. In the present study, splenectomy did not affect growth of primary Panc02, 4T1 and E0771 tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The spleen, a secondary lymphoid organ, may be involved in the anti-tumour immune response, and a relationship between splenectomy and lung metastasis has been reported (31,32). We noticed that at 12 days after inoculation, the percentage and absolute number of CD3 + T cells were significantly increased in the spleen.…”
Section: Discussionmentioning
confidence: 52%
“…Splenectomy has been reported to serve an important role in the antitumor immune response in an experimental model (27)(28)(29). Higashijima et al (28) reported that splenectomy enhances liver metastasis through an increase in forkhead box P3 mRNA in the liver.…”
Section: Univariate Analysismentioning
confidence: 99%
“…Higashijima et al (28) reported that splenectomy enhances liver metastasis through an increase in forkhead box P3 mRNA in the liver. On the other hand, Sonoda et al (29) reported that the metastatic lung nodules were significantly smaller in size and number in the subject group that underwent splenectomy compared with the control group in a mouse metastasis model and concluded that this occurred due to splenectomy-induced decreases in serum levels of vascular endothelial growth factor and basic fibroblast growth factor. In the present study, patients with (y)pT3N0 EGJ cancer who underwent splenectomy had improved DSS compared with those who did not undergo splenectomy.…”
Section: Univariate Analysismentioning
confidence: 99%